2015
DOI: 10.1038/jhg.2015.96
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-133a inhibits ischemia-reperfusion-induced cardiomyocyte apoptosis by targeting DAPK2

Abstract: To examine microRNA-133a (miR-133a) endogenous expression in cardiomyocytes after ischemia-reperfusion (I/R) injury and study the effects of miR-133a overexpression on I/R injury-induced cardiomyocyte apoptosis. Dual-Luciferase Reporter Assay detected dynamic expression of miR-133a. In an in vitro hypoxia-reoxygenation (HR) injury model and an in vivo rat model of I/R injury, rat cardiomyocytes were transfected with miR-133a mimic to test the effects of miR-133a overexpression on apoptosis. MiR-133a and Death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Moreover, miR-133a attenuates hypoxia-induced apoptosis by suppressing caspase-8 signals via its inhibition of the TAGLN2 gene in cardiomyocytes [61]. It was recently demonstrated that miR-133a inhibits injury-induced cardiomyocyte apoptosis by targeting the DAPK2 gene [62]. In our study, caspase-3 activity was decreased by miR-133a via EVs in C 2 C 12 cells under conditions of cell stress.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, miR-133a attenuates hypoxia-induced apoptosis by suppressing caspase-8 signals via its inhibition of the TAGLN2 gene in cardiomyocytes [61]. It was recently demonstrated that miR-133a inhibits injury-induced cardiomyocyte apoptosis by targeting the DAPK2 gene [62]. In our study, caspase-3 activity was decreased by miR-133a via EVs in C 2 C 12 cells under conditions of cell stress.…”
Section: Discussionsupporting
confidence: 52%
“…Thus far, numerous miRNAs have been reported to be associated with myocardial I/R injury by regulating target genes, including miR-451, miR-133a, and Lin28a (11)(12)(13). The current study investigated the potential role of miR-613 in myocardial I/R injury and results indicated that the level of miR-613 expression decreased by 43% in H9c2 cells after H/R treatment in comparison to the level of expression in the controls.…”
Section: Discussionmentioning
confidence: 88%
“…Li et al (2015) reported that miR-133a overexpression might inhibit I/R injury-mediated cardiomyocyte apoptosis by targeting death associated Figure 5 The effect of MAPK6 on the function of propofol on cell apoptosis induced by H/R. miR-133a-5p was a member of the miR-1/ miR-133 cluster of miRNAs.…”
Section: Discussionmentioning
confidence: 99%